"It Is Too Much for Us": Direct and Indirect Costs of Disability Amongst Working-Aged People with Disabilities in Dhaka, Bangladesh and Nairobi, Kenya. Issue 2 (3rd April 2022) - Banks, Lena Morgon; Hameed, Shaffa; Abu Alghaib, Ola; Nyariki, Emily; Olenja, Joyce; Kulsum, Umma; Karim, Rafiul; Shakespeare, Tom
ABSTRACT: Globally, people with disabilities face a heightened risk of poverty. Drivers of poverty include exclusion from work and other livelihood activities (indirect costs) and disability-related direct costs – such as for rehabilitation, personal assistance and assistive devices – that are required for participation and functioning. This research explores sources of direct and indirect costs, their impact and mitigation strategies using 42 in-depth interviews with working-aged people with disabilities in Nairobi, Kenya and Dhaka, Bangladesh. This research finds that people with disabilities and their households face high direct costs, such as for healthcare, assistive devices, transportation and accommodations at school and work, and indirect costs, such as un- and underemployment and lower salaries when working. Many direct costs were unmet, or covered through out-of-pocket spending, although social protection in Kenya was also an important strategy. Unmet direct costs frequently led to higher future indirect costs. Direct and indirect costs could cause financial strain, decreased participation, health and wellbeing, particularly when unaddressed. Challenges mitigating costs included not just insufficient income, but also lack of decision-making power within the household and insufficient information on and poor availability of needed goods, services and opportunities – factors which should be considered in the design of interventions.